2008
DOI: 10.3748/wjg.14.3254
|View full text |Cite
|
Sign up to set email alerts
|

Change of intestinal mucosa barrier function in the progress of non-alcoholic steatohepatitis in rats

Abstract: AIM:To explore the change of intestinal mucosa barrier function in the progress of non-alcoholic steatohepatitis (NASH) in rats. METHODS: Thirty-two Sprague-Dawley (SD) rats were randomly divided into control group and model group. Rats in the control group were given normal diet, and rats in the model group were given fat-rich diet. Eight rats in each group were killed at end of the 8th and 12th wk, respectively. The levels of endotoxin, D-xylose, TG, TC, ALT and AST, intestinal tissue SOD and MDA as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…The authors also found an increased rate of small bowel overgrowth within these patients, as measured by glucose breath testing, suggesting that alterations in the microbiome may have contributed to disruption of gut barrier integrity. Similarly, studies of mouse models have found correlations between hepatic inflammation and measures of loss of intestinal barrier integrity, which further supports the hypothesis that loss of intestinal barrier integrity influences the pathogenesis of NAFLD and possibly NASH . Loss of this barrier function theoretically could expose the liver to increased levels of bacterial pro‐inflammatory products such as LPS, as well as toxic bacterial metabolic by‐products, including ethanol and other VOC such as ethanol, acetone and butanoic acid, among others.…”
Section: Resultssupporting
confidence: 56%
“…The authors also found an increased rate of small bowel overgrowth within these patients, as measured by glucose breath testing, suggesting that alterations in the microbiome may have contributed to disruption of gut barrier integrity. Similarly, studies of mouse models have found correlations between hepatic inflammation and measures of loss of intestinal barrier integrity, which further supports the hypothesis that loss of intestinal barrier integrity influences the pathogenesis of NAFLD and possibly NASH . Loss of this barrier function theoretically could expose the liver to increased levels of bacterial pro‐inflammatory products such as LPS, as well as toxic bacterial metabolic by‐products, including ethanol and other VOC such as ethanol, acetone and butanoic acid, among others.…”
Section: Resultssupporting
confidence: 56%
“…An increase in intestinal permeability has been observed in some studies with NAFLD patients, but not in all (Table 1). However, an increased intestinal permeability in animal models and elevated endotoxin levels in both animals and NAFLD patients (34,37,(76)(77)(78)(79), further support the role of a decreased barrier function.…”
Section: Possible Contributing Factors and Mechanisms Of Intestinal Ementioning
confidence: 83%
“…Occludin was regarded as one of the most important tight junction-associated structural proteins in the intestines and played a very important role in keeping physical barrier of intestinal mucosa49. Studies from Luca Miele et al .…”
Section: Discussionmentioning
confidence: 99%